Pieces of eight : more archaeology of piracy - Ewen, Charles R. (University Press of Florida, 2016)
There is little to distinguish the pirate from the average sailor in the archaeological record. Virtually every pirate-related site yet excavated would not be identified as such without the accompanying historical record. The contributors to this volume combine both material culture and archival research to confirm the exploits of pirates and the ships they sailed.